Conformational implications of asparagine-linked glycosylation. - Imperiali, B (1995)
The effects of cotranslational protein modification on the process of protein folding are poorly understood. Time-resolved fluorescence energy transfer has been used to assess the impact of glycosylation on the conformational dynamics of flexible oligopeptides. The peptide sequences examined are selected from glycoproteins of known three-dimensional structure. The energy transfer modulation associated with N-linked glycosylation is consistent with the glycopeptides sampling different conformational profiles in water. Results show that glycosylation causes the modified peptides to adopt a different ensemble of conformations, and for some peptides this change may lead to conformations that are more compact and better approximate the conformation of these peptides in the final folded protein. This result further implies that cotranslational glycosylation can trigger the timely formation of structural nucleation elements and thus assist in the complex process of protein folding.